Molecular Population Genetics and Evolution of the Chagas’ Disease Vector Triatoma infestans (Hemiptera: Reduviidae) - Garcia, Beatriz Alicia (2013)
Triatoma infestans (Klug) is the main vector of Chagas’ disease in the Southern Cone of Latin America between the latitudes 10° S and 46° S. The long-term effectiveness of the control campaigns is greatly dependent upon the vector population structure. Mitochondrial DNA (mtDNA) genes have been used in a number of T. infestans population genetic analyses. However, the maternally inherited markers as well as nuclear ribosomal DNA analyzed until the present exhibited low or limited levels of variation. Analyses based on microsatellite markers strongly supported the existence of some type of stratification in T. infestans populations and supported the hypothesis of vector population recovery from survivors of the insecticide-treated areas, highlighting the value of population genetic analyses in assessing the effectiveness of Chagas’ disease vector control programmes. Although phylogeographic studies have generally suggested a Bolivian Andean origin of T. infestans, they recovered two reciprocal monophyletic groups of T. infestans and Bolivian populations who were not basal as expected for an ancestral group. In addition, a non-Andean origin could not be excluded by mtDNA genealogies that included sylvatic bugs from Gran Chaco. On the other side, mitochondrial and microsatellite markers supported the hypothesis of two independent migration events of colonization and secondary contacts in southern South America. Since the phylogenetic analyses remain inconclusive, more sequences, not only from mitochondrial genes but also from nuclear genes, need to be examined.